Two-Group Theory of the Feynman-Alpha Method for Reactivity Measurement in ADS - Lénárd Pál; Imre Pázsit (Science and Technology of Nuclear Installations)
The theory of the Feynman-alpha method, which is used to determine the subcritical reactivity of systems driven by an external source such as an ADS, is extended to two energy groups with the inclusion of delayed neutrons. This paper presents a full derivation of the variance to mean formula with the inclusion of two energy groups and delayed neutrons. The results are illustrated quantitatively and discussed in physical terms.